2020
DOI: 10.3389/fimmu.2020.575179
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium Compound Disinfectants Reduce Lupus-Associated Splenomegaly by Targeting Neutrophil Migration and T-Cell Fate

Abstract: Hypersensitivity reactions and immune dysregulation have been reported with the use of quaternary ammonium compound disinfectants (QACs). We hypothesized that QAC exposure would exacerbate autoimmunity associated with systemic lupus erythematosus (lupus). Surprisingly, however, we found that compared to QAC-free mice, ambient exposure of lupus-prone mice to QACs led to smaller spleens with no change in circulating autoantibodies or the severity of glomerulonephritis. This suggests that QACs may have immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…The use of QAC disinfectants has increased with the pandemic [ 11 ] resulting in increased exposure to QACs in the home [ 12 ], and most likely in the workplace as well. In animal studies, we have demonstrated declines in male and female reproduction [ 16 , 17 ], severe defects in neural development [ 18 ], and alterations in both neutrophil and T-cell phenotype and activity [ 19 ]. We also have found that chronic oral dosing during breeding and gestation resulted in maternal absorption and transfer of C12 BAC and C16 BAC across the placenta to the fetus, and disrupted lipid homeostasis in the neonatal brain [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of QAC disinfectants has increased with the pandemic [ 11 ] resulting in increased exposure to QACs in the home [ 12 ], and most likely in the workplace as well. In animal studies, we have demonstrated declines in male and female reproduction [ 16 , 17 ], severe defects in neural development [ 18 ], and alterations in both neutrophil and T-cell phenotype and activity [ 19 ]. We also have found that chronic oral dosing during breeding and gestation resulted in maternal absorption and transfer of C12 BAC and C16 BAC across the placenta to the fetus, and disrupted lipid homeostasis in the neonatal brain [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using in-vitro studies on both human and mouse cell lines, we found that QACs increase inflammation, disrupt mitochondrial function, alter estrogen signaling, and inhibit cholesterol synthesis [ [13] , [14] , [15] ]. In mice, we have shown that normal use of a disinfectant containing a mixture of BAC and DDAC in the vivarium inhibited reproduction, caused birth defects, and altered immune function [ [16] , [17] , [18] , [19] ]. With gestational exposure, BACs cross the placenta to alter cholesterol and lipid homeostasis in mouse neonatal brains [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the splenic size was not different between JAX and in-house female mice, probably because our facility shared a cage washing machine with adjacent facilities that did use QAC disinfectants, leading to ambient exposure of in-house mice to QACs. However, although we did not investigate male mice in the previous QAC study (30), our observation that the male splenic size was significantly larger in in-house versus new JAX mice may be explained by a QACassociated decrease in splenomegaly. Furthermore, the differences in previous housing conditions may explain why JAX mice after arriving at our facility harbored significantly different gut microbiotas from our in-house mice during the first month.…”
Section: Discussionmentioning
confidence: 74%
“…In parallel, QACs upregulated splenic neutrophil expression of checkpoint protein programmed death-ligand 1 (PD-L1). Moreover, QAC exposure dampened the activation of splenic T cells and increased apoptosis of effector T-cell populations, thereby mitigating SLE-associated lymphadenopathy in this mouse model ( 418 ). Furthermore, while the phenotype of reduced splenomegaly and lymphadenopathy is an indication of protection against a mouse model of SLE, our findings also indicate that even ambient exposure to QACs could alter neutrophil and T-cell phenotypes, functions, and their fate, raising concerns about the immunotoxicity of these chemicals.…”
Section: Hygiene As An Environment Factormentioning
confidence: 97%